Impact of Race and Social Determinants on Operative Management of Distal Radius Fractures in Medicare Patients - Nicole J. Newman-Hung, MD; Amil R. Agarwal, BA; Ambika E. Paulson, MD; Uma Srikumaran, MD, MBA, MPH; Dawn Laporte, MD; Lauren E. Wessel, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Operative fixation of distal radius fractures (DRFs) in high-demand patients may provide functional benefit, particularly in the setting of significant displacement. Whether social determinants of health (SDOH) and race impact treatment remain unclear. The purpose of this study was to determine whether adverse SDOH modifiers and race are independent predictors of surgical intervention for DRF. Methods:. A retrospective analysis was conducted using the Medicare Standard Analytical Files of the PearlDiver database of patients with a DRF from 2007 to 2016. Univariate and multivariable regression analyses were performed to observe whether race and adverse SDOH variables were independent predictors of undergoing open reduction internal fixation (ORIF) within 3 weeks of a new diagnosis of DRF after controlling for age and fracture type. Results:. The average patient age was 76.3 years. A total of 10,697 (13.1%) patients underwent ORIF. Patients who underwent ORIF were less likely to have negative economic and social modifiers of SDOH and had lower odds of being non-White. Patients who underwent surgery also had higher odds of being younger, White, female, and having a type III open fracture. Conclusions:. In the Medicare population, non-White race and adverse economic and social modifiers of SDOH were independent predictors of undergoing nonoperative treatment of DRF after controlling for age and fracture type. Future studies are needed to further elucidate the nuanced effects of race and SDOH on the management of DRFs.